Phygital learning ecosystems and places beyond 2030 - Carlo Giovannella; Giuseppe Roccasalva (Interaction Design and Architecture(s))
The aim of this article is to provide designers of future smart learning ecosystems with a cultural framework of reference, and a set of inspirational principles consistent with it, that can act as stimulus and guide. The framework is introduced by a critical analysis of the evolution that educational spaces have undergone in recent centuries in function of both pedagogical requirements and process optimisation, up to the most recent experiments. It is then illustrated the meaning, sense and purpose that should be attached to a smart learning ecosystem (SLE) identified with: a) the development of the competences needed by the students to find their place in the society and playing a propositive role, and b) the wellbeing of the actors involved in the learning process. Finally the cultural paradigm (people in place centred design), the pedagogical framework of reference (learning by being) and the didactic approach (P3BL: problem-project-process based learning) that should serve as a source of inspiration for the design of future learning places, and/or for the renovation of existing ones, are discussed. Four the guiding principles, discussed in the article, that are expected to be followed: centrality and openness of the spaces to the territory of reference, functional specificity, flexibility, affordance. Also discussed are the qualities – sensitive, enabling, engaging – that should characterise the integration of new technologies within the spaces of SLEs to make them phygital, together with the trends that are expected to characterise the phygital transformation in the future.